Proteomic Analysis Reveals Dab2 Mediated Receptor Endocytosis Promotes Liver Sinusoidal Endothelial Cell Dedifferentiation. Issue 1 (December 2017) - Lao, Yuanxiang; Li, Yanyan; Hou, Yufang; Chen, Huahai; Qiu, Bintao; Lin, Weiran; Sun, Aihua; Wei, Handong; Jiang, Ying; He, Fuchu
Abstract Sinusoidal dedifferentiation is a complicated process induced by several factors, and exists in early stage of diverse liver diseases. The mechanism of sinusoidal dedifferentiation is poorly unknown. In this study, we established a NaAsO2 -induced sinusoidal dedifferentiation mice model. Liver sinusoidal endothelial cells were isolated and isobaric tag for relative and absolute quantitation (iTRAQ) based proteomic approach was adopted to globally examine the effects of arsenic on liver sinusoidal endothelial cells (LSECs) during the progression of sinusoidal dedifferentiation. In all, 4205 proteins were identified and quantified by iTRAQ combined with LC-MS/MS analysis, of which 310 proteins were significantly changed in NaAsO2 group, compared with the normal control. Validation by western blot showed increased level of clathrin-associated sorting protein Disabled 2 (Dab2) in NaAsO2 group, indicating that it may regulate receptor endocytosis, which served as a mechanism to augment intracellular VEGF signaling. Moreover, we found that knockdown of Dab2 reduced the uptake of VEGF in LSECs, furthermore blocking VEGF-mediated LSEC dedifferentiation and angiogenesis.